Transcriptional insights on the incomplete cytoplasmic maturation and developmental potential of oocytes cultured without granulosa cells in mice - Yibo Wang; Yichuan Zhang; Tianjie Li; Yun Ren; Ping Zhou; Lin Fu; Chenxi Xiao; Ziying Huang; Hanji Huang; Wenfeng Xie; Yuxin Luo; Yanan Qi; et al. (BMC Genomics)
Abstract Background Oocyte maturation is crucial for female fertility and embryonic development, encompassing nuclear and cytoplasmic maturation. Supportive cells of follicles, such as granulosa cells, are essential for oocyte growth and maturation. Oocytes can achieve nuclear maturation without granulosa cells during in vitro maturation (IVM). However, there is still a higher chance of incomplete cytoplasmic maturation for these oocytes with mature nuclei compared with oocytes cultured with granulosa cells. Oocytes with incomplete cytoplasmic maturation have lower fertilization rates and developmental potential than mature ones, although underlying mechanisms are poorly understood. Identifying key genes and signaling pathways associated with oocyte cytoplasmic maturation can help further elucidate the maturing process of oocytes and understand the impact of immature oocytes on embryonic development, throwing insights into the strategy to improve the success rate of assisted reproductive technologies. Results Our study investigated murine oocytes maturing with and without granulosa cells. IVM without granulosa cells yielded oocytes with lower nuclear maturation rates than IVM with granulosa cells and in vivo maturation (IVO). Even though oocytes could achieve nuclear maturation without granulosa cells, they showed incomplete cytoplasmic maturation featuring higher levels of reactive oxygen species, lower mitochondrial density, and higher proportions of cells with abnormal distributions of cortical granules. Of note, oocytes with immature and mature cytoplasm had distinct transcriptional profiles. In the immature oocytes, we observed a deficient mRNA restoration of genes in crucial regulatory pathways of cellular growth and division, potentially affecting embryonic development. Differentially expressed genes (DEGs) between immature and mature oocytes were identified to be highly expressed in different pre-implantation stages, such as the MII oocyte, the 8-cell stage, and the ICM stage. Identified DEGs were enriched in key regulatory pathways of fertilization and embryonic development, such as energy and metabolic pathways. These observations indicated that the impeded development potential of oocytes with immature cytoplasm might be the result of abnormal gene expressions during oocyte maturation. Conclusions We show that granulosa cells are important for both nuclear and cytoplasmic maturation of oocytes. Abnormal gene expression in oocytes with incomplete cytoplasmic maturation may be associated with potential defects in fertilization and embryonic development.